Hubungan antara Budaya Organisasi terhadap Senjangan Anggaran di Sekolah Inklusif dengan Peran Komitmen Organisasi sebagai Variabel Intervening - Risma Wira Bharata; Siti Afidatul Khotijah; Nibras Anny Khabibah (President University Press, 2021)
This study aims to determine the relationship between organizational culture and budgetary slack, as well as the role of organizational commitment as an intervening variable for inclusive schools in Gunungkidul Regency. This survey research was conducted by dividing a questionnaire consisting of 6 questions on budgetary slack, 23 items on organizational culture, and 9 questions on organizational commitment. This study used a sample of 110 respondents who determined the sample based on purposive sampling. Path analysis in this study was used as data analysis using PLS 3.0 software. This study shows the results that with a t-statistic value of 1,822 the influence of organizational culture on organizational gaps, with a t-statistic value of 1,731 the influence of organizational culture on organizational commitment. Meanwhile, with the t-statistic 0.822, organizational commitment has no effect on budgetary slack.